Aerobic scope predicts dominance during early life in a tropical damselfish. (16th June 2014) - Killen, Shaun S.; Mitchell, Matthew D.; Rummer, Jodie L.; Chivers, Douglas P.; Ferrari, Maud C. O.; Meekan, Mark G.; McCormick, Mark I.; Grindstaff, Jennifer
Summary A range of physiological traits are linked with aggression and dominance within social hierarchies, but the role of individual aerobic capacity in facilitating aggression has seldom been studied. Further, links previously observed between an individual's metabolic rate and aggression level may be context dependent and modulated by factors such as social stress and fcompetitor familiarity. We examined these issues in juvenile Ambon damselfish, Pomacentrus amboinensis, which display intraspecific competition for territories during settlement on coral reefs. Individuals were measured for routine metabolic rate, aerobic scope (AS) and anaerobic capacity using intermittent‐flow respirometry before dyadic dominance contests. Post‐contest, fish were measured for metabolic rate in isolation and while interacting with their previous competitor or a stranger in adjacent transparent respirometers. In arena contests, AS was correlated with aggression and dominance, while routine metabolic rate and anaerobic capacity were not related to dominance. Post‐contest, subordinates showed a rise in metabolic rate and decrease in available AS, presumably due to social stress. Dominants increased metabolic rate in the presence of a previous competitor, possibly due to the stresses of hierarchy maintenance. Metabolic rate during aggressive interactions did not approach that measured during exhaustive exercise, suggesting individuals do not fully utilise their AS during aggression. A greater AS may, however, allow faster post‐contest recovery. These results demonstrate a link between AS and dominance during intraspecific competition for territory. Selection on AS could therefore follow, either indirectly through correlations with other traits influencing resource‐holding potential, or directly if AS carries benefits important for territory acquisition or holding, such as an enhanced capacity to cope with socially induced stress.